A diagnostic dilemma: early repolarization syndrome associated with ventricular fibrillation - Yavuzer Koza; Zakir Lazoğlu; Kamuran Kalkan; Serdar Sevimli (KARE Publishing, 2014)
An early repolarization (ER) pattern, characterized by J-point elevation, slurring of the terminal part of the QRS and ST-segment elevation, is a common finding on the 12-lead electrocardiogram. It has been suggested that J-point elevation, which was considered benign for many years, may play a critical role in the pathogenesis of idiopathic ventricular fibrillation (VF). Recent studies have shown that an ER pattern in inferior leads or inferolateral leads is associated with increased risk for life-threatening arrhythmias. We report the case of a 52-year-old man with no structural heart disease whose electrocardiogram showed type 2 ER pattern (with evidence of J-point and ST-segment elevation in electrocardiogram leads II, III, and aVF). The patient presented with VF.